The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/buildings11120646
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Decisive Causes of PPP Project Disputes in China

Abstract: Disputes are inevitable in public-private partnership (PPP) projects and generate great losses of time and money in practice. If an in-depth understanding of dispute sources can be obtained beforehand, the process of PPP may become more smooth. This paper aims to identify and assess the causes of PPP disputes between the public and private sectors. First, 15 causes are explored based on the PPP litigation cases from China Judgments Online. Second, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In anticipation of operational intervention, understanding the root cause of the contractual dispute is crucial. 19,20 Based on the Pareto principle, 21 the author discovered that 20% of the factors instigating disputes in PPP contracts in public universities are significant while 80% of the causes are negligible. The result in Table 1 was elucidated based on the responses of the participants to five-point Likert scale questions, and the analysis done to determine the mean values of the variables.…”
Section: • Identification Of Causes Of Disputementioning
confidence: 99%
“…In anticipation of operational intervention, understanding the root cause of the contractual dispute is crucial. 19,20 Based on the Pareto principle, 21 the author discovered that 20% of the factors instigating disputes in PPP contracts in public universities are significant while 80% of the causes are negligible. The result in Table 1 was elucidated based on the responses of the participants to five-point Likert scale questions, and the analysis done to determine the mean values of the variables.…”
Section: • Identification Of Causes Of Disputementioning
confidence: 99%
“…Chou and Lin (2013) investigated the implication of dispute avoidance before bidding and starting PPP projects with classification and ensemble models, and identified a tendency to dispute with high prediction power of about 84%. Zheng et al (2021b) suggested strategies or implications of PPPs' contracting parties contribute to public (e.g. the establishment of a lifelong liability mechanism), private 16), stakeholder management action plan (8) and stakeholder monitoring (9).…”
Section: Dispute Root Causes In Pppsmentioning
confidence: 99%
“…Zheng et al. (2021b) also placed fifteen causes of disputes in PPP projects into the reason and result categories.…”
Section: Avoiding Disputes: Leading Ppp To Desirable Performancementioning
confidence: 99%
See 2 more Smart Citations